Monitoring training fatigue with the orthostatic heart rate test during 9 weeks of intensified training in biathletes - Thomas, C. E.; Karavirta, L.; Kinnunen, H.; Laing, S. J. (World Congress of Performance Analysis of Sport IX, 2012)
In monitoring the effects of training and non-training stress on an athlete, parameters that are inexpensive and practical to measure, with minimal disturbance to the training process, are preferred (Urhausen & Kindermann, 2002). Moreover, it is essential that such measures be accurate enough to give athletes and sport coach`s scientific feedback on an athletes` preparedness to train; thus facilitating the training process and helping to determine the point at which training becomes maladaptive (Brink et al., 2010). In the present study, the terms overreaching (OR) and overtraining (OT) will be used to express a disturbance in the stress-regeneration balance (Rietjens et al., 2005). The aim of this investigation was to determine the effectiveness of the orthostatic heart rate (OHR) test when tracking alterations in training stress during 9 weeks of intensified training in biathletes. In order to determine this, previously identified functional, haematological and hormonal markers of OT/ OR were examined during the 9-week period and the results correlated with that of the OHR indices. Eleven trained biathletes (age [mean ±SEM]: Male 22.2 ±0.9 yr, Female 28.2 ± 2.0 yr; height: Male 182.3 ±3.1 cm, Female 163.2 ±3.2 cm; VO2max: Male 63.9 ±2.7 ml.kg-1.min-1, Female 54.5 ±1.6 ml.kg-1.min-1) underwent intensified training over a 9 week period. Intravenous blood samples, OHR, heart rate variability (HRV) and a 30 minute standardized sub-maximal treadmill test (STT) were undertaken at baseline, during the three training blocks (pre-, mid-, post-; training blocks duration 17 ± 2.2 days) and at the end of the 9 week period. Training intensity increased during the 9 week period, TRIMP [mean]: (Block 1: 693.5, Block 2: 514.4, Block 3: 1025.12), Training hours [mean ±SEM]: (Block 1: 47.6 ±0.28 Block 2: 30.8 ±0.16 Block 3: 68.8 ±0.55 ), Average session RPE (Block 1: 14.6 ±0.03, Block 2: 16.7 ±0.03, Block 3: 14.9 ±0.04 ). During the STT, intensified training periods showed significant signs of overload identified with a decreased submaximal heart rate (HR: P < 0.05), decreased submaximal blood lactate (BL: P < 0.05), minimal changes in the HRV low frequency output (LF: P < 0.05) and low frequency/high frequency ratio (LF:HF: P < 0.05), increased cortisol levels (P < 0.05) and reduced testosterone (P < 0.05) and free testosterone/cortisol ratio levels (FCTR: P < 0.05). Furthermore the results showed increased OHR resting heart rate levels (RHR: P < 0.05) and a minimally decreased OHR 30 seconds post standing (P30: P < 0.05). When correlated with the RHR index of the OHR test, strong correlations were found for submaximal HR (-0.71), submaximal BL (-0.72), testosterone (-0.86), FTCR (-0.71), as well as haemoglobin (Hb) (-0.88), and haematocrit (Hct) (-0.85) levels over the 9-week training period. Moreover, the P30 index revealed moderate correlations for submaximal HR (0.56), submaximal BL (0.34), LF (0.46), HF (.33), testosterone (0.41), Hb (0.49) and Hct (0.53) over the same training period. However, the peak upon standing (PH) index only produced a moderate correlation with cortisol (0.49) whereas correlations with all other indices were weak; submaximal HR (-0.21), submaximal BL (-0.21), testosterone (-0.17), FTCR (-0.17), haemoglobin (Hb) (-0.07), and haematocrit (Hct) (0.02) Collectively, these findings suggest that the morning RHR index remains one of the most effective and practical non-invasive tools to use by coaches and athletes when monitoring training status and preparedness to train.